Effect of Fat Particle-to-SVF Ratio on Graft Survival Rates in Rabbits. Issue 5 (May 2015) - Ni, Youdi; He, Xiaosheng; Yuan, Zhijian; Liu, Maolin; Du, Hongying; Zhong, Xiaochun
Abstract : Objective: This study aimed to compare the graft survival rates of various ratios of fat particles to stromal vascular fraction (SVF) in rabbits. Methods: Fifteen purebred white rabbits of the same brood were used. In the study, the grafts of equal weight (0.8 g) were mixtures of fat particles with various proportions of SVF (1/3, 1/4, 1/5, and 1/6) to form 4 treated groups (I, II, III, and IV), whereas merely fat particles formed 1 control group. They were randomly autoimplanted into subcutaneous pockets on both sides of the dorsal midlines of the rabbits. Animals were killed 3 months after surgery. The grafts were harvested and weighed. Comparisons were performed between the groups for survival rates. Results: The treated group II (fat particle-to-SVF ratio was 3:1) revealed the greatest weight maintenance in all of the groups, showing the greatest survival rate [87.94% (1.30%), P < 0.01 or P < 0.05]. Conclusions: It was suggested that the optimal fat particle-to-SVF ratio might be 3:1, with a low resorption rate.